Lack of Maternal Social Capital Increases the Likelihood of Harsh Parenting - Sangwon Kim; Desmond K. Runyan; Yanghee Lee (MDPI AG, 2022)
Does low maternal social capital increase the likelihood of parents using harsh parenting behaviors? We analyzed random digit dial telephone survey data from 661 female primary caregivers across Colorado. Positive reports of the use of either physically or psychologically harsh parenting methods were classified as harsh parenting. Absence of social capital was assessed within the family and the community; lack of social capital within the family was measured in terms of an absence of support from a partner and an additional caregiver. Absence of social capital within the community was measured as lack of interpersonal resources from neighbors and religious activities. Nearly 30% admitted to one or more physically harsh parenting behaviors in the prior year, and 85.8% reported at least one psychologically harsh parenting behavior. Lower levels of neighborhood connectedness were associated with physically harsh parenting (odds ratio = 1.50). Conflict between partners (odd ratio = 2.50) and the absence of an additional caregiver (odds ratio = 1.88) increased psychologically harsh parenting. One practical implication is that mental health and medical providers should help new parents value, access, or develop social networks within the community to prevent children from experiencing harsh parenting.